2011
DOI: 10.1371/journal.pcbi.1002304
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Binding in Human and Mouse Embryonic Stem Cells Identifies Conserved Enhancers Active in Early Embryonic Development

Abstract: Transcription factors are proteins that regulate gene expression by binding to cis-regulatory sequences such as promoters and enhancers. In embryonic stem (ES) cells, binding of the transcription factors OCT4, SOX2 and NANOG is essential to maintain the capacity of the cells to differentiate into any cell type of the developing embryo. It is known that transcription factors interact to regulate gene expression. In this study we show that combinatorial binding is strongly associated with co-localization of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 45 publications
3
39
0
Order By: Relevance
“…Although this mechanism may maintain enhancers in a low-level open state, the absence of critical tissue-specific transcription factors could prevent downstream gene activation. Enhancers would become active and increase target gene expression only in tissues where the sufficient combination of transcription factors is available (Göke et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Although this mechanism may maintain enhancers in a low-level open state, the absence of critical tissue-specific transcription factors could prevent downstream gene activation. Enhancers would become active and increase target gene expression only in tissues where the sufficient combination of transcription factors is available (Göke et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Sox21 has not been previously studied in the early mouse embryo but is known to inhibit expression of the trophectoderm (TE) master gene Cdx2 in ES cells and is important for reprogramming (Kuzmichev et al, 2012). Furthermore, Sox21 expression is directly regulated by Sox2 (Chakravarthy et al, 2011;Kuzmichev et al, 2012;Mallanna et al, 2010), and its regulatory region is bound by Oct4 (Chakravarthy et al, 2011;Gö ke et al, 2011), which has heterogeneous nuclear-cytoplasmic kinetics at the 4-cell stage (Plachta et al, 2011). Together, this suggests that the heterogeneous Sox21 expression may itself be regulated by heterogeneous Oct4 and/or Sox2 activity in the embryo.…”
Section: Temporal and Spatial Gene Expression Patterns In Single Cellmentioning
confidence: 99%
“…We focused on genes that are highly variable at the 4-cell stage and are targeted by Oct4 and/or Sox2 (including Sox21 [Chakravarthy et al, 2011;Gö ke et al, 2011]) and searched for subsets of genes whose expression patterns are coordinated. To this aim, the matrix of pairwise Spearman correlation coefficients was computed and hierarchical clustering was carried out (R function ''hclust,'' default options).…”
Section: Testing For Enrichment Of Oct4 and Sox2 Targets Among Highlymentioning
confidence: 99%
“…These studies suggest that OCT4, SOX2, and NANOG can physically interact with each other and coordinately regulate target genes in some cases. Additionally, Goke and colleagues reported that combinatorial binding sites of the OCT4/SOX2/NANOG were more conserved between mouse and human ESCs than individual binding sites were [40,41].…”
Section: Discussionmentioning
confidence: 99%